قدرة الشركات الصناعية الأردنية على تطبيق عمليات الهندسة العكسية في عملياتها الإنتاجية: دراسة ميدانية - العفيف، جمال حسن عيسى (جامعة جرش, 2017)
شهد العالم في الآونة الأخيرة ثورة ريادية كبيرة في مجال عمليات التصنيع كان الغاية منه إيجاد أسلوب صناعي مبتكر، وعلى مختلف الأصعدة المحلية والعالمية. حدى الأمر بالشركات المتقدمة صناعياً بالبحث عن أسلوب صناعي فكري والذي تم بالفعل، بإيجاد ما يعرف بأسلوب الهندسة العكسية، والذي كانت الغاية منه تحسين وتطوير منتجات الشركات الصناعية لكونه أسلوب قائم على عملية تحليل أبعاد ومكونات مشاهدة أو مجموعة مشاهدات واستخلاص طرق تصنيعية جديدة فضلاً عن إمكانية القيام بها بصورة عكسية مقارنة مع عملية التصميم الطبيعية، يعني أن هذا نهج يعتمد على عكس عمليات الهندسة الاعتيادية عن طريق تحليل المعرفة المكثفة الذي يحتويها المنتج المراد إجراء عليه عمليات الهندسة العكسية، يتضمن هيئة الكشف عن خطوات وعناصر وأساليب التي من خلالها تمت عملية التصنيع. لذلك تكون مجتمع الدراسة من جميع الشركات الصناعية المساهمة العامة المدرجة في بورصة عمان والبالغ عددها حتى نهاية عام 2015 (65) شركة صناعية. وقد تم اختيار عينة تضم (56) شركة إما الفئة المستهدفة في الدراسة فكانت تتضمن كل من مديري الدوائر والأقسام الخاصة بالأمور المالية والإنتاج والمبيعات والتسويق والمشتريات والتزويد في كل شركة. وكانت أهم نتائج الدراسة تتمحور بوجود تبني واضح لمنهج الهندسة العكسية في الشركات الصناعية الأردنية، حيث تبين أن الشركات تقوم بإجراء اختبارات على المنتج الجديد لتأكد من نجاح المنتج من فشله قبل البدء بعمليات الإنتاج، كما ويتم التأكد من إن الخامات والمواد الأولية الداخلة في التصنيع متوفرة في الأسواق. أما أهم توصيات فتتجسد بضرورة إن تعمل الشركة على دراسة المنتج المنافس من خلال تفكيكه والتعرف على مكوناته من حيث التركيب والتجميع، وتحديد ما يجب توافره لتصنيعه. بحيث تتزامن هذه العملية مع التعرف على وظيفة كل جزء يدخل في إنتاج المنتج لديها من أجل العمل على تطويرها واختصار الأجزاء غير الضرورية وإضافة القيمة للمنتج.
The world has recently witnessed a major innovation revolution in the field of manufacturing, which was aimed at creating an innovative industrial method, and at various local and international levels. this lead most advanced industrial companies to search for an industrial method of thinking, which has already been found in reverse engineering. the goal of it was the improvement and development of industrial products companies because it is based on the analysis of components and drawing new manufacturing methods as well as the possibility of doing it in reverse engineering in comparison with the normal design process this means that this approach depends on the reverse operations through the usual intensive knowledge analysis which is contained in the product to be made to it reverse engineering operations, which includes detection steps, that detects the elements and methods through which the manufacturing process has been made. Therefore, the study community consisted of all industrial public shareholding companies listed on the Amman Stock Exchange and travel until the end of 2015 which are (65) Industrial Company. A sample of (56) companies was selected, the target group in the study included the managers of the departments and sections of the financial affairs, production, sales, marketing, procurement and supply in each company. The main results of the study focused on the existence of a clear adoption of the reverse engineering method in the Jordanian industrial companies. It was found that the companies are conducting tests on the new product to see the success or the failure of the product before they start their production operations, plus they are making sure that the raw materials used in manufacturing are available in the market. The most important recommendations of the study is the need of the company to start studying the competitor product through the dismantling and identifyication of its components in terms of installation and assembly, and determine what elements need to be available to have it manufactured. So that this process coincides with the identification of the function of each part that contributes to the product production that develops and shorten the unnecessary parts and add value to the product
Keywords: الشركات الصناعية -- الإنتاج الصناعي -- الهندسة العكسية -- الأردن